Praxiologia e representação social sobre formação de professores nas licenciaturas da UFPI - Queiroz, Nilza Maria Cury (2011)
At this investigation it was analyzed the content and the organization of the social representation on the object teachers education, built by teachers of degree courses from Universidade Federal do Piauí(Ufpi), understanding such representation articulated to the teaching habitus of these educators of teachers, what takes under consideration the position that they hold in the structure of the national field and in the subfield of teachers education. For that, it is searched: a) to emphasize the properties of the place in which the trainers act Ufpi as the office of those field and subfield; b) to understand who are the trainers, that is, to grasp the teaching habitus of the trainers with a view of its origin, social trajectory and the specifics of their position in the analyzed field and the subfield and c) to know what they think about their work object, that is, identify and articulate the content and the organization of the social representation analyzed with their properties of field and subfield agents. The research includes the specific degree courses of the Campus Ministro Petrônio Portella , from Teresina(PI), and it was applied to 134 professors of degree courses from this Campus. The data collect joined to the participants happened on the second period of 2008 and on the first semester of 2009. The starting point of the study is the corroboration that the reform of Ufpi degree courses, determined by the legislation and stablished at this Institution in 2005, altered a little the previous situation. It is comprehended that Ufpi and its structures of teachers education as a trainer institution, is limited by the national academic field and by the subfield of teachers education. From this last one, it was listed some of its properties, to show that it is about an academic subfield in construction process. It is emphasized division of the subfield, that separates the trainers into two subgroups the ones who dedicate themselves to the specific education on the contents and those ones who are specialized on pedagogical education placed in antagonistic position and competing by the symbolic power of imposing the meaning and the sense of the teachers education in the degree courses. To understand the comprehension of the problem, it is searched for the models that are in the root of the construction of the University and its project of teachers education in the degree courses, to clarify the matrixes in which the social representation searched is stablished. The theoretical referential articulates the contributions of Moscovici, the theory of social representations, and of Bourdieu, with the concepts that compose its praxeology, as habitus, social field, capital, symbolic power and others, as well as their interpreters and continuators, as Domingos Sobrinho. From the literature about the university and teachers education, it was used Dermeval Saviani, Luiz Antônio Cunha, Maria Isabel da Cunha and Mirian Jorge Warde, besides others. Plurimethodological procedures were adopted, combining associative techniques adjusted to the access to the social representations, and a classic technique, a questionnaire about teaching habitus. The condition is that the teachers build different social representation of the object teachers education because of the distinct positions that they occupy in the structure of the academic field and the subfield of the teachers education. The reached positions in the field and subfield are due to the differences in the origin and social trajectory of these agents, who, therefore, have different teaching habitus from which they build their social representation about their work object. It is highlighted that the teaching habitus and the social representation of two subfields, identified by the belongings to different dimensions of the teachers education in the degree courses, they have similarities and, also, differences. These ones permit to support that the subjects are holders of distinct teaching habitus that conceive different practices, struggles, tensions and conflicts around the sense of teachers education